Upaya Meningkatkan Hasil Belajar IPS Materi Berbagai Pekerjaan Menggunakan Model Pembelajaran Problem Based Learning Kelas IV SDN 4 Lahat Selatan - Robili; Lia Rismawati (Lembaga Bale Literasi, 2025)
This classroom action research aims to improve the learning outcomes of fourth grade students of SD Negeri 4 Lahat Selatan in the subject of Social Studies on the material